A Prattler's tale: Bengal, marxism, governance - Mitra, Ashok; Bhattacharya, Sipra (Kolkata : Samya, 2007)
Autobiographical memoirs of an economist, politician, and writer from Calcutta, who was formerly finance minister in the state of West Bengal, India, ruled by the Communist Party of India (Marxist).
includes bibliographical references and index.
Keywords: ECONOMIST- BIOGRAPHY